In situ synthesis of TiO2/NC on cotton fibers with antibacterial properties and recyclable photocatalytic degradation of dyes. Issue 31 (8th July 2022) - Chen, Wei; Feng, Xiaolin; Zhang, Danyin; Lu, Fangfang; Wang, Hairong; Tan, Jiacheng; Xu, Qiao; Liu, Yongkun; Cao, Zhihai; Su, Xiuping
Abstract : A cotton fabric/titanium dioxide-nanocellulose (TiO2 -Cot.) flexible and recyclable composite material with highly photocatalytic degradation of dyes and antibacterial properties was synthesized. Abstract : A cotton fabric/titanium dioxide-nanocellulose (TiO2 -Cot.) flexible and recyclable composite material with highly photocatalytic degradation of dyes and antibacterial properties was synthesized. During the preparation process, nano-TiO2 particles were synthesized through an in situ strategy and grown on cotton fiber, and were wrapped with cellulose nanocrystals (NC). The prepared TiO2 -Cot. was characterized by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The SEM and EDS results showed that nano-TiO2 particles were evenly distributed on the fiber surface. The prepared TiO2 @Cot. has excellent photocatalytic efficiency of 95.68% for MB and 92.77% for AR under weak ultraviolet irradiation over 6 h. At the same time, it has excellent antibacterial activity against S. aureus and E. coli . The stability and reusability of the materials were also investigated.